SIGNAGE KAMPUS BERBASIS DESIGN THINKING DI FAKULTAS TEKNIK UNILAK - Hafson, Haikal; Iman, Al; Hariandini, Tesa Beta (Department of Interior Design, Faculty of Engineering, Lancang Kuning University, Indonesia, 2025)
The Faculty of Engineering at Universitas Lancang Kuning currently lacks an integrated signage system, leading to navigation difficulties and reduced academic efficiency. This study aims to design a signage prototype that is informative, communicative, and aligned with the faculty’s Malay cultural identity, while ensuring accessibility for all users. A qualitative method with a design thinking approach was used, covering the stages of empathize, define, ideate, prototype, and test. Data were collected through field observations and semi-structured interviews with students and lecturers. The prototypes, both physical and digital, were tested through limited usability testing. Results indicate that the signage design should include a clear information hierarchy, the university’s corporate color palette, readable typography, and strong cultural elements. Signage placement was also designed to be accessible and easy to locate. The implementation of this signage is expected to improve wayfinding, enhance user experience, and strengthen the professional image of the Faculty of Engineering.